2019
DOI: 10.1002/smll.201900583
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Boosts Defective Vanadium Oxide from Semiconducting to Metallic Merit

Abstract: 2D metal oxide nanosheets have attracted substantial attention for various applications owing to their appealing advantages. Yet, the exploration of effective methodology for fabrication of metallic 2D metal oxides with a high concentration of N dopants in a scalable manner remains challenging. Herein, a topochemical strategy is demonstrated on vanadium oxide nanosheets by combining 2D nanostructuring, heteroatom‐doping, and defect engineering for modulating their intrinsic electronic structure and greatly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The 1.77 × 10 4 -fold improvement in conductivity for VN/CNTs compared with V 2 O 5 · n H 2 O was realized, which can be mainly ascribed to the nitridation and carbonization process. The enhancement of the conductivity is in good agreement with the previous reports (2.4 × 10 –2 S m –1 for V 2 O 5 · n H 2 O, 1.67 × 10 6 S m –1 for VN, and 4.16 × 10 4 S m –1 for N-doped CNT). Further, the fabrication technique for the flexible strain sensor is illustrated in Figure a. A micropatterned poly­(methyl methacrylate) (PMMA) strip-type (with the size of tens of micrometers) template was used assisted by a barrier film with the identical hollowed patterns.…”
Section: Resultssupporting
confidence: 88%
“…The 1.77 × 10 4 -fold improvement in conductivity for VN/CNTs compared with V 2 O 5 · n H 2 O was realized, which can be mainly ascribed to the nitridation and carbonization process. The enhancement of the conductivity is in good agreement with the previous reports (2.4 × 10 –2 S m –1 for V 2 O 5 · n H 2 O, 1.67 × 10 6 S m –1 for VN, and 4.16 × 10 4 S m –1 for N-doped CNT). Further, the fabrication technique for the flexible strain sensor is illustrated in Figure a. A micropatterned poly­(methyl methacrylate) (PMMA) strip-type (with the size of tens of micrometers) template was used assisted by a barrier film with the identical hollowed patterns.…”
Section: Resultssupporting
confidence: 88%
“…Partial density of state (PDOS) was employed to reveal the electrical conductivity derived from different oxygen defect structures. [ 52 ] As shown in Figure 6d, T‐Nb 2 O 5− x with oxygen vacancies on position 1 has a bandgap of 1.365 eV, much lower than that of pristine T‐Nb 2 O 5 (1.844 eV). In comparison, T‐Nb 2 O 5− x with oxygen vacancies on positions 2 and 3 displays the approximate bandgaps with that of pristine T‐Nb 2 O 5 .…”
Section: Resultsmentioning
confidence: 99%
“…14,15,[191][192][193] An alternative method to anionically-doping vanadium oxide materials is through the substitution of oxide moieties for non-oxygen anions such as halides, [194][195][196][197][198][199][200] sulfides, [201][202][203] or nitrides. 204,205 Experimental and computational investigations have shown that both physical and chemical properties are significantly influenced by the introduction of these anionic dopants. Indeed, numerous studies have revealed that increasing the concentration of oxygen-deficient vanadium centres in V x O y greatly enhances the catalytic activity of these materials toward small molecule activation processes as these vacant sites are proposed to be the active sites of catalysis.…”
Section: Anionic Dopants In Molecular Vanadium Oxide Assembliesmentioning
confidence: 99%